Blues and Roots/Rue and Bluets : A Garland for the Southern Appalachians - Williams, Jonathan, 1929-2008 (Book collections on Project MUSE., 1985)
Jonathan Williams's poetry has been described as brilliant, sensuous, lyrical, quirky, suave, vital, joyful, sardonic, melodious, passionate, alive, pyrotechnic. This new, much enlarged edition of Blues and Roots displays all of the above. Williams has tramped the Appalachian Trail for decades, botanizing, jotting down specimens of authentic American speech, graffiti, superstitions, and nostrums-always curious, alert, and affectionately attentive. Blues and Roots focuses on the linguistic horizon of Appalachia in lyrics of wonder and light, of wit and comic incongruity, in found poems of the s.